A new approach to palynostratigraphy of the middle–late Famennian Gafo Formation, southern sector of the Pulo do Lobo Domain, SW Iberia (Portugal and Spain). (27th August 2022) - Mendes, Márcia; Pereira, Zélia; Vaz, Nuno; Díez-Montes, Alejandro; Matos, João X.; Albardeiro, Luis; Fernandes, Paulo; Jorge, Raul; Chew, David
Abstract: New palynological results from the Gafo Formation (southern sector of the Pulo do Lobo Domain, South Portuguese Zone) are integrated with recently studied sections and drillholes from the Portuguese and Spanish sectors. A total of 44 samples were studied, 27 of which were positive for palynomorph taxonomy. This research revealed well preserved palynological assemblages, including 73 spore species allocated to 28 genera, four acritarch genera, three prasinophyte algae genera plus common chitinozoan remains. Some additional forms were retained under open nomenclature. From this, the first complete age determination for the Gafo Formation in Portugal and Spain was achieved, indicating a middle Famennian ( Grandispora gracilis–Grandispora famenensis, GF Biozone) to a late Famennian ( Grandispora echinata, VH Biozone) age. A greywacke sample from the same Gafo Formation was dated by U–Pb zircon geochronology and a maximum depositional age of 369 ± 2.5 Ma was obtained. A correlation between these palynological and U–Pb zircon data and the palynoflora assemblages of previous authors was made, as well as with the ages of felsic volcanic rocks found intercalated in the Gafo Formation, confirming the complex stratigraphy of Pulo do Lobo Domain. The results are consistent with stratigraphic mapping and structural interpretations, allowing a middle–late Famennian age (GF and VH Biozone) to be assigned to the Gafo Formation sedimentary rocks. This work has also contributed to a reinterpretation of Gafo Formation depositional facies correlatives (e.g. the Santa Barbara Group in Spain) as being the same lithological unit.